Pertumbuhan dan Hasil Empat Genotip Tanaman Cabai Rawit (Capsicum frutescens L.) di Lahan Ultisol Bangka Belitung - Ramadhani, Ashriyah; Lestari, Tri; Mustikarini, Eries Dyah; Syukur, Muhammad (Jurnal Agroekoteknologi, 2025)
Marginal land such as Ultisol land can be utilized for cayenne pepper production. Cayenne pepper that have the potential to have high adaptation in Ultisol land have the opportunity to be used as superior varieties. This research aims to determine cayenne pepper genotypes that are able to grow well on Ultisol land. Adaptive genotypes of cayenne pepper plants in ultisol soils need to be selected. The research was conducted in Febuary-December 2024. The research location at the Experimental and Research Garden, University of Bangka Belitung. The research method used experimental method with single factor Randomized Group Design. The treatments used were four genotypes of cayenne pepper plants consisting of 2 lines (F5 372340-10-9-2K and F6 372340-7-28-6-2) and 2 varieties (Bonita and Lestari) which were repeated 6 times. The results showed that the four genotypes tested had different growth and crop yields in Ultisol land. The genotype of cayenne pepper plants had different results, namely the F6 strain 372340-9-7-28-6-2 weighing 596 g, F5 372340-10-9-2K weighing 27 g, the Lestari variety 1907.36 g, and the Bonita variety 3513.03 g per plot. The Bonita variety has good growth in Ultisol land based on the number fruity diameter, yield per plant and yield per plot.